Mathematical Modeling of Temperature and Rainfall Driven Dengue Transmission in Sudurpashchim Province, Nepal - Pant, Yagya Raj; NKharel, Nilam; Bhatta, Amrit; Chaudhary, Puja (Api Journal of Science, 2025)
Dengue disease dynamics highly depends on environmental temperature as its transmitting vectors-Aedes aegypti and Aedes albopictus mosquitoes are poikilothermal. Temperature influences mosquitoes’ key traits, including biting rate, oviposition rate, development rates of aquatic and adult stages, and lifespan. Rainfall in proper amounts, together with suitable temperatures, significantly supports egg hatching and growth of aquatic stage by creating breeding sites. In regions like Nepal, where seasonal variations in temperature and rainfall occur, mosquito population fluctuates seasonally, causing vector-borne diseases like dengue fever to similarly rise and fall. This paper develops a climate-sensitive mathematical model for dengue transmission in Sudurpashchim Province, Nepal, integrating effects of seasonal change in temperature and rainfall on mosquito life traits. We analyze the dengue dynamics model using symbolic and numerical tools to better understand disease patterns. Numerical simulations indicate that increasing mosquito mortality and reducing carrying capacity of environment to limit aquatic phase population are effective strategies for controlling and diminishing dengue outbreaks.